American Wigeon Anas americana vigilance behaviour on suburban golf courses - Berl, Jacob L. (Wildfowl, 2013)
Behavioural data were recorded from flocks of wintering American Wigeon Anas americana on a southern Californian (USA) golf course to test whether vigilance was related to levels of local human activity. The study site was subject to high rates of human activity, which provided an opportunity to evaluate waterfowl anti-predatory response (vigilance) when presented with frequent disturbance stimuli. Overall, human activities had no significant effect on individual vigilance behaviour while flocks grazed on golf course fairways. Vigilance patterns were instead influenced by the distance at which flocks grazed from water, flock size and the sex of the birds. Furthermore, vigilance constituted < 7 % of the ducks’ activity budget, less than that reported for American Wigeon and Eurasian Wigeon Anas penelope in more natural environments. This suggests that the ducks did not increase time spent in vigilance in response to high rates of human activity, but may benefit from favourable foraging opportunities associated with golf course and other human-modified habitats.